2023
DOI: 10.1038/s41467-023-37272-8
|View full text |Cite
|
Sign up to set email alerts
|

Cable bacteria with electric connection to oxygen attract flocks of diverse bacteria

Abstract: Cable bacteria are centimeter-long filamentous bacteria that conduct electrons via internal wires, thus coupling sulfide oxidation in deeper, anoxic sediment with oxygen reduction in surface sediment. This activity induces geochemical changes in the sediment, and other bacterial groups appear to benefit from the electrical connection to oxygen. Here, we report that diverse bacteria swim in a tight flock around the anoxic part of oxygen-respiring cable bacteria and disperse immediately when the connection to ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In benthic microbial fuel cells, cable bacteria may interact with other electrogenic bacteria (e.g., in the family Desulfuromonadaceae) through extracellular electron transfer. Recently, Bjerg et al discovered through Raman microscopy that diverse bacteria form a tightly packed flock around the anoxic part of cable bacteria in a freshwater sediment enrichment culture [25]. Further analysis indicated that these flocking bacteria included sulfide oxidizers, which might transfer electrons to cable bacteria for sulfur oxidation.…”
Section: Electron Transfer In Microbial Sulfur Oxidationmentioning
confidence: 99%
See 2 more Smart Citations
“…In benthic microbial fuel cells, cable bacteria may interact with other electrogenic bacteria (e.g., in the family Desulfuromonadaceae) through extracellular electron transfer. Recently, Bjerg et al discovered through Raman microscopy that diverse bacteria form a tightly packed flock around the anoxic part of cable bacteria in a freshwater sediment enrichment culture [25]. Further analysis indicated that these flocking bacteria included sulfide oxidizers, which might transfer electrons to cable bacteria for sulfur oxidation.…”
Section: Electron Transfer In Microbial Sulfur Oxidationmentioning
confidence: 99%
“…Meanwhile, a recent study has discovered that cable bacteria mediating electrogenic sulfur oxidation can enhance the bioavailability of pyrene and promote the enrichment of degradative bacteria, thereby facilitating the removal of pyrene [82]. Therefore, the unique biological characteristics of cable bacteria endow them with a significant role in global biogeochemical cycles, and the LDET is advantageous for a variety of applications, such as microbial fuel cells for electricity generation or bioremediation of organic contaminants in sediments [25].…”
Section: Significance Of Microbial Electron Transfer In the Environme...mentioning
confidence: 99%
See 1 more Smart Citation
“…Mapping longer sequences (70 bp to 1 Mbp), share similar features such as long-read support and split alignment [180] SAMtools (v1.19.2) Manipulating and analyzing sequence alignment data, crucial for post-processing and downstream analysis of metagenomic data [181,182] De Novo Metagenome Assembly MEGAHIT (v1.2.9)…”
Section: Bioinformatics Analysis For Metagenomicsmentioning
confidence: 99%
“…Cable bacteria are surrounded by a veil of microorganisms that swim around them (Thorup et al, 2021 ). These veil microorganisms dispersed once the cable bacterium was physically cut (Bjerg et al, 2023 ). In this volume, Lustermans et al investigate whether the presence of the microbial veil is connected to a cable bacteria progression and senescence in its environment and the subsequent geochemical changes.…”
Section: Cable Bacteriamentioning
confidence: 99%